Pengaruh Media Audio Visual Terhadap Hasil Belajar Siswa pada Materi Pertumbuhan Hewan di Kelas III SD Muhammadiyah 37 Tanjung Selamat - Supiyanti, Supiyanti; Ramadhan, Nuri; Herdyana, Thessa (Medan Resource Center, 2024)
This research aims to examine the impact of audio-visual media on student learning outcomes in the subject of animal growth for third-grade students at SD Muhammadiyah 37 Tanjung Selamat. The study employed an experimental method with a